Synthesis, conformational studies, and biological properties of phosphonomethoxyethyl derivatives of nucleobases with a locked conformation via a pyrrolidine ring - Pohl, Radek; Poštová Slavětínská, Lenka; Eng, Wai Soon; Keough, Dianne T; Guddat, Luke W; Rejman, Dominik (Organic & biomolecular chemistry, 2015)
Systematic structure-activity studies on a diverse family of nucleoside phosphonic acids has led to the development of potent antiviral drugs such as HPMPC (CidofovirTM), PMEA (AdefovirTM), and PMPA (TenofovirTM), which are used in the treatment of CMV-induced retinitis, hepatitis B, and HIV, respectively. Here, we present the synthesis of a novel class of acyclic phosphonate nucleotides that have a locked conformation via a pyrrolidine ring. NMR analysis of these compounds revealed that the pyrrolidine ring has a constrained conformation when in the cis-form at pD < 10 via hydrogen bonding. Four of these compounds were tested as inhibitors of the human and Plasmodium falciparum 6-oxopurine phosphoribosyltransferases. The most potent has a Ki of 0.6 μM for Plasmodium falciparum HGXPRT.
Keywords: farmaceutická chemie; Animals; Plasmodium falciparum; vodíková vazba; Kinetics; Pentosyltransferases; Organophosphonates; Hydrogen-Ion Concentration; Adenine; pyrrolidiny; Structure-Activity Relationship; lidé; Chemistry, Pharmaceutical; Pyrrolidines; hypoxanthin; magnetická rezonanční spektroskopie; antimalarika; organofosfonáty; Protein Conformation; adenin; racionální návrh léčiv; Oxygen; pentosyltransferasy; Hydrogen Bonding; konformace proteinů; Drug Design; vztahy mezi strukturou a aktivitou; Hypoxanthine; zvířata; Magnetic Resonance Spectroscopy; koncentrace vodíkových iontů; kinetika; Antimalarials; kyslík; Humans